Pengembangan E-Modul Pada Mata Pelajaran Komputer dan Jaringan Dasar Untuk Kelas X Program Keahlian Teknik Komputer Dan Jaringan Di SMK Negeri 2 Malang Dengan Model Pengembangan Four-D - Lutfiani Akhmadi; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Computers and basic networks are one of the subjects taught at Vocational High School 2 Malang in the field of Computer and Network Engineering. The problems found during the implementation include, teaching materials sourced from the internet, no use of teaching modules, learning values are still below the minimum limit. The solution to solving the problems is through designing a Flip PDF Professional 2.4.9.18 E-Module with the Four-D development model. The data collection technique is done through observation, interviews, questionnaires, and tests. According to material experts 1 and 2, the level of validity and feasibility of E-Modules is 98.00% and 94.20%, while according to media experts 1 and 2 are 66.00% and 91.00% and are very good categories. The output of the E-Module is in the form of the average pre-test and post-test values of 65.46 and 82.53, with the results of different tests t getting a significance value <0.05. Based on the results of the analysis, E-Module is said to be effective as indicated by an increase in student achievement based on differences in the mean values of the pre-test and post-test